Effects of exercise training on exercise capacity of patients with interstitial lung disease: a systematic review and meta-analysis - Qian Zhao; Nan Mo; Rui Li; Tian Tian Wei; WenJin Xu; Jie Wang; ShanShan Li; Huifang Zhu; Guiling Miao (BMC Pulmonary Medicine)
Abstract Background The effects of exercise-based interventions in patients with interstitial lung disease ( ILD) are not fully understood. To better understand the effects of exercise training on functional exercise capacity, we conducted a meta-analysis. Objective This systematic review and meta-analysis aimed to evaluate the effects of exercise training on the functional exercise capacity of adults with ILD. Methods We searched the PubMed, Embase, Web of Science, and Cochrane Library databases from inception to July 2024 and the reference lists of the included articles. All RCT that included exercises and outcomes assessed the functional exercise capacity of adults with ILD. Data were pooled with the mean difference or standardized, random-effect model, and 95% confidence intervals ( CI) using RevMan V.5.4. We also used Cochrane risk-of-bias tool and GRADE to rate the quality of the evidence. Results Sixteen RCTs with 899 participants were included. Exercise interventions significantly improved 6MWD ( ILD: MD = 35.88 m(m), 95% CI: 22.65–49.10, P < 0.00001; IPF: MD = 28.84 m, 95% CI: 14.73–42.95, P < 0.0001), enhanced peak work rate ( ILD: MD = 3.79 watts, 95% CI: 0.66–6.92, P < 0.05; IPF: MD = 5.98 watts, 95% CI: 2.34–9.63, P < 0.01), VO2 peak ( IPF: MD = 0.84 ml/kg/min, 95% CI: 0.18–1.50, P < 0.05), alleviate dyspnea ( ILD:MD = -0.46, 95% CI:-0.68,-0.23, P < 0.0001; IPF: MD = -0.33, 95% CI:-0.63,-0.03, P < 0.05), depressive symptoms ( ILD:MD = -1.94, 95% CI:-3.67, -0.22, P < 0.05), and improved health-related quality of life( HRQoL) ( ILD:MD = -6.39, 95% CI:-8.67,-4.12, P < 0.00001; IPF: MD = -6.58, 95% CI:-9.42,-3.75, P < 0.00001). In the subgroup with different intervention durations, functional exercise and quality of life improvements were maintained during the short-to long-term follow-up. However, dyspnea was significant only after 6 months of intervention. Conclusion Exercise training demonstrated significant improvements in exercise tolerance and HRQoL in patients with ILD, particularly IPF, with sustained benefits observed over long-term intervention. Additionally, exercise alleviates dyspnea and depressive symptoms, with effects maintained during short to medium-term interventions. These findings support the safe incorporation of exercise training into standard therapeutic regimens for ILD. Future studies should prioritize the optimization of high-quality exercise protocols tailored to specific ILD subtypes and determine optimal strategies for maximizing clinical benefits.